FRI0583 VALIDATION OF THE MODIFIED FATIGUE IMPACT SCALE IN DANISH PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Junker, C. I.; Duch, K.; Dreyer, L.; Gregersen, J. W.; Kristensen, S.
Abstract : Background: Patients with systemic lupus erythematosus (SLE) experience significant fatigue, a debilitating symptom associated with reduced quality of life. A simple, reliable multidimensional method for assessing fatigue has not yet been validated for Danish patients with SLE. Objectives: The primary objective was to study the internal consistency, test-retest reliability, and construct validity (convergent and discriminant validity) of the multidimensional Modified Fatigue Impact Scale (MFIS) in patients with SLE. The secondary objective was to investigate the contribution of disease activity and organ damage to fatigue. Methods: Data from the "Bio and Genome Bank Study in Centre for SLE and Vasculitis" obtained through routine visits were used. Fatigue was assessed using the MFIS and Short Form 36 (SF36). Internal consistency of the MFIS was assessed with Cronbach's alpha (α). Test-retest reliability was evaluated using the intraclass correlation coefficient (ICC). Construct validity was studied using Spearman's rank correlation coefficient (rs ) and Principal Component Analysis (PCA) between MFIS and SF36 vitality (VT-SF36) and mental health (MH-SF36) subscales. Association between MFIS and disease activity and organ damage was estimated with Spearman's rank correlation coefficient. Results: The study included 30 patients with SLE. Internal consistency of the MFIS was excellent with Cronbach's α = 0.97 for the complete scale. Excellent test-retest reliability was found with ICC = 0.95 (95% confidence interval: 0.88-0.98, p < 0.05). Construct validity was confirmed by Spearman's correlation (VT-SF36: rs = −0.73, p < 0.001 (Fig. 1 ). MH-SF36: rs = −0.74, p < 0.001 (Fig. 2 )) and PCA with explained variance from the first two principal components (PC) (VT-SF36: PC1 = 60.2%, PC2 = 8.5%. MH-SF36: PC1 = 58.5%, PC2 = 7.4%). No significant correlation was found between the MFIS and SLEDAI (rs = 0.04, p = 0.84) or SLICC Damage Index (rs = 0.32, p = 0.08). Conclusion: The present study found the multidimensional assessment of fatigue with MFIS to be a reliable and valid instrument in SLE. The MFIS might provide more detailed information about fatigue in future studies. In agreement with some previous studies we found no association between fatigue and SLEDAI or SLICC which raises questions about the cause of this symptom. Further and larger studies are needed to investigate if any association between fatigue and disease components exist. Disclosure of Interests: None declared